2013
DOI: 10.1016/j.ygyno.2013.04.143
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic heterogeneity in endometrial cancer: Evidence from a Gyneco- logic Oncology Group trial

Abstract: Objective-Although the epidemiology of typical endometrial carcinomas (grades 1-2 endometrioid or Type I) is well established, less is known regarding higher grade endometrioid or non-endometrioid carcinomas (Type II). Within a large Gynecologic Oncology Group trial (GOG-210), which included central pathology review, we investigated the etiologic heterogeneity of endometrial cancers by comparing risk factors for different histologic categories.Methods-Based on epidemiologic questionnaire data, risk factor asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Endometrial carcinoma (EC) is the most common female genital tract malignancy in the United States comprising a heterogeneous group of tumors that includes endometrioid carcinomas (EECs), serous carcinomas (ESCs), clear cell carcinomas, and other less common histologic subtypes (1). Molecular mapping of endometrial tumors in the last decade has shown that EECs and ESCs have been associated with mutations in PTEN, ARID1A, PIK3CA, KRAS, and CTNNB1, and TP53, PPP2R1A, and FBXW7, respectively (2,3).…”
mentioning
confidence: 99%
“…Endometrial carcinoma (EC) is the most common female genital tract malignancy in the United States comprising a heterogeneous group of tumors that includes endometrioid carcinomas (EECs), serous carcinomas (ESCs), clear cell carcinomas, and other less common histologic subtypes (1). Molecular mapping of endometrial tumors in the last decade has shown that EECs and ESCs have been associated with mutations in PTEN, ARID1A, PIK3CA, KRAS, and CTNNB1, and TP53, PPP2R1A, and FBXW7, respectively (2,3).…”
mentioning
confidence: 99%
“…The comparison with literature data is more delicate because of adjunction of grade 3 endometrioid EC to type II EC during the study period, because they are considered as having similar prognosis (35)(36). When performing our analyses, grade 3 endometrioid EC was included in type II ECs as reported in the latest recommendations.…”
Section: Discussionmentioning
confidence: 99%